2014
DOI: 10.1021/am506198b
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Large-Scale and Thickness-Modulated MoS2 Nanosheets

Abstract: Two-dimensional MoS2 is a promising material for next-generation electronic and optoelectronic devices due to its unique electrical and optical properties including the band gap modulation with film thickness. Although MoS2 has shown excellent properties, wafer-scale production with layer control from single to few layers has yet to be demonstrated. The present study explored the large-scale and thickness-modulated growth of atomically thin MoS2 on Si/SiO2 substrates using a two-step sputtering-CVD method. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 53 publications
(81 reference statements)
4
123
1
Order By: Relevance
“…The FWHM of the EBI sample was higher than that of the exfoliated monolayer MoS 2 (FWHM of E 1 2g : 2.8 cm −1 , FWHM of A 1g : 4.7 cm −1 ) 30 . However, the crystallinity of our 1 min EBI-treated sample at room temperature was superior to that of sputtered MoS 2 films (FWHM of E 1 2g : ~50 cm −1 , FWHM of A 1g : ~14 cm −1 ) with a substrate temperature of 300 °C 20 and comparable to that of 5.4 nm thick MoS 2 films (FWHM of E 1 2g : ~12 cm −1 , FWHM of A 1g : ~14 cm −1 ) grown at 600 °C with a hybrid process of sputtering combined with the CVD method 16 . Especially, instead of the long tail for the E 1 2g peak that is commonly observed in the Raman spectra of a MoS 2 film from the sputtering process 20–22 , a relatively short tail was observed in our results.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The FWHM of the EBI sample was higher than that of the exfoliated monolayer MoS 2 (FWHM of E 1 2g : 2.8 cm −1 , FWHM of A 1g : 4.7 cm −1 ) 30 . However, the crystallinity of our 1 min EBI-treated sample at room temperature was superior to that of sputtered MoS 2 films (FWHM of E 1 2g : ~50 cm −1 , FWHM of A 1g : ~14 cm −1 ) with a substrate temperature of 300 °C 20 and comparable to that of 5.4 nm thick MoS 2 films (FWHM of E 1 2g : ~12 cm −1 , FWHM of A 1g : ~14 cm −1 ) grown at 600 °C with a hybrid process of sputtering combined with the CVD method 16 . Especially, instead of the long tail for the E 1 2g peak that is commonly observed in the Raman spectra of a MoS 2 film from the sputtering process 20–22 , a relatively short tail was observed in our results.…”
Section: Resultsmentioning
confidence: 89%
“…In PVD methods, similar problems related with scaling up and the operating temperature still exist. A hybrid sputtering process combined with CVD, which first deposits a Mo film and then progresses to sulfurization via a chemical reaction with sulphur vapour, has recently been reported, but it need sufficient heating of the substrate to over 600 16 or 800 °C 17 . There have been attempts to carry out deposition and sulfurization simultaneously by using a Mo target in hydrogen sulphide (H 2 S) gas 18 and vaporised sulphur ambient 19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the conduction band energy level of bulk MoS 2 is less negative than that of TiO 2 . Fortunately, nanoscale MoS 2 exhibited quantum confinement effects as some research reported [16][17][18][19]. Owing to the confinement effects, the band gap of nanoscale MoS 2 can be increased significantly and the energy level of conduction band is higher than that of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Compared with the Raman spectra of PANI, the 3D-MoS 2 -PANI nanoflowers exhibited two other Raman characteristic bands at 405 and 379 30 cm -1 (Fig.2 curve b), corresponding to the A 1g and E 1 2g modes of MoS 2 nanostructure, respectively. 31,32 Above results indicated the successful synthesis of 3D-MoS 2 -PANI nanoflowers. …”
Section: Characterization Of Different Nanomaterialsmentioning
confidence: 86%